EVALUASI PELAKSANAAN PEMBELAJARAN BAHASA ARAB BERBASIS KURIKULUM 2013 KELAS V SD AL-AMIN CEMANI GROGOL SUKOHARJO - Rania Ahrefani, Salsabila; Putra , Sudarmadi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Learning Implementation Plan is an important component of learning. However, in practice, it is known that teachers at Al-Amin Elementary School still consider lesson plans to be only administrative completeness requirements and teachers still miss some of the implementation components in the implementation components of lesson plans. This study aims to evaluate the implementation of the Arabic language learning process at SD Al-Amin Cemani Grogol Sukoharjo. This research is a qualitative descriptive study. The research subject is an Arabic teacher. Data collection using the method of observation, interviews and document study. Then data analysis using data reduction, data presentation and data verification. The research data was checked for the validity of the data using the triangulation technique. The results of this study indicate that in the process of implementing Arabic language learning using the 2013 curriculum which was carried out by the Arabic teacher at Al-Amin Cemani Grogol Sukoharjo Elementary School, the implementation of learning starting from preliminary activities, core activities and closing activities has been carried out, but the implementation of learning is written in RPP is not all implemented by the teacher during the learning process in the field. The teacher also has several obstacles in the implementation of learning, however the teacher has a strategy to overcome these obstacles.